PENGARUH KEPUASAN KERJA, DISIPLIN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA ANGGOTA DALMAS (Studi Pada Subdit Dalmas Polda Jateng) (Students' Journal of Economic and Management, 2013)
Purpose of the implementation of this study is to examine and analyze the effect of job satisfaction, organizational commitment and work discipline to performance Dalmas Member. The research was conducted at the Central Java Police Sub Dalmas Members who totaled 135 pirposive using the criteria of the lowest rank of Brigadier. Results of regression testing obtained results Adjusted R Square of 0.741, meaning that the change of variable performance can be explained by the variables of job satisfaction, work discipline, and organizational commitment of 74.1%. whereas for the F test show that jointly job satisfaction, work discipline and organizational commitment affect the performance.Based on the known partial regression testing job satisfaction affects the performance with significance 0.000 <0.05, the performance of the work discipline of significance 0.012 <0.05 and organizational commitment affect the performance of the 0.000 significance. <0.05. It is identified that all the hypotheses accepted or proven.Keywords: work satisfaction, organizational commitment and performance